Factors associated with thrombocytopenia in patients with dengue fever: a retrospective cohort study - Marcus T Silva; Luciane Cruz Lopes; Izabela Fulone; Bruna M Castilho; André R R Freitas (BMJ Open)
Objective Some patients with dengue fever tend to develop thrombocytopenia during the course of infection and are thus vulnerable to haemorrhagic manifestations and other complications. However, the factors associated with the development of thrombocytopenia are unknown. We aimed to identify factors associated with an increased risk of thrombocytopenia and haematological changes in patients with confirmed dengue fever.Design Retrospective cohort study.Setting Brazilian multicentre primary care databases.Participants 387 patients had positive laboratory serological confirmation of dengue infection during 2014. The data were identified from two databases: Notification of Injury Information System (SINAN) and Municipal Laboratory.Main outcome measure The presence of thrombocytopenia (platelet count <1 50×109/L). The associations of factors that predisposed patients to thrombocytopenia and haematological changes were analysed using logistic regression. ORs and 95% CIs were calculated.Results Among 387 patients, 156 had both dengue and thrombocytopenia. The risk factors associated with thrombocytopenia included male sex (OR: 1.77, 95% CI: 1.16 to 2.71, p=0.007), age of 46–64 years (OR: 2.20, 95% CI: 1.15 to 4.21, p=0.009) or ≥65 years (OR: 3.02, 95% CI: 1.40 to 6.50, p=0.002), presence of leucopenia (OR: 6.85, 95% CI: 4.27 to 10.99, p<0.001) and high mean corpuscular haemoglobin (MCH) levels (OR: 2.00, 95% CI: 1.29 to 3.12, p=0.005).Conclusion Older age, male sex, presence of leucopenia and high MCH levels were identified as risk factors associated with the development of thrombocytopenia in this population.